Chemistry-climate model SOCOL: a validation of the present-day climatology - T. Egorova; E. Rozanov; V. Zubov; E. Manzini; W. Schmutz; T. Peter (Copernicus Publications, 2005)
In this paper we document 'SOCOL', a new chemistry-climate model, which has been ported for regular PCs and shows good wall-clock performance. An extensive validation of the model results against present-day climate data obtained from observations and assimilation data sets shows that the model describes the climatological state of the atmosphere for the late 1990s with reasonable accuracy. The model has a significant temperature bias only in the upper stratosphere and near the tropopause at high latitudes. The latter is the result of the rather low vertical resolution of the model near the tropopause. The former can be attributed to a crude representation of radiation heating in the middle atmosphere. A comparison of the simulated and observed link between the tropical stratospheric structure and the strength of the polar vortex shows that in general, both observations and simulations reveal a higher temperature and ozone mixing ratio in the lower tropical stratosphere for the case with stronger Polar night jet (PNJ) and slower Brewer-Dobson circulation as predicted by theoretical studies.